Peningkatan Kreatifitas Umkm Dan Kompetensi Wirausaha Melalui Edukasi Ekspor - Vivi Iswanti Nursyirwan; Sasmita Sari Ardaninggar; Asih Handayani (Abdimisi, 2022)
Micro, small and medium enterprises (MSMEs) are the backbone of a nation's economy. However, the journey to becoming an important pillar of the national economy is not without obstacles. The author's observation sees that MSMEs are constrained by HR management, especially with regard to the competence of MSME HR. In the current VUCA era, competence is important for SMEs. In addition, another important thing is the marketing of MSME products. Go-Export is part of international marketing that needs to be socialized to MSME actors so that MSME actors at least get knowledge, skills and in the end can form relevant attitudes to support their business performance. The results of our observations show that many MSMEs have adapted well to grow, but on the other hand, we also find that many MSMEs do not know "know-how", experience managerial incomprehension, both human resource management and financial management, as well as marketing management. In this activity, we have organized entrepreneurship development for MSMEs who are members of the online market community. This activity focuses on export education. This activity is also accompanied by business assistance so that after the PKM activities are carried out, MSME actors will still be able to consult businesses, so that the creativity and competence of MSMEs can increase. Our practical output: there is an increase in the creativity and entrepreneurial competence of MSME actors so that MSME actors can be more competitive in competing in today's all-digital era. The results of the test on this PKM activity showed that there was an increase in the average value of MSME business actors in Depok City, originally the average value was 6.84 to an average value of 7.96, or an increase of 6.96%.